Keysha's Cookies Sdn Bhd / Siti Nurkhalishah Muslee - Muslee, Siti Nurkhalishah (2020)
Keysha's Cookies Sdn Bhd is a form of business-based partnership five members holding key positions such as General Manager, Administration Manager, Finance Manager, Operation Manager and Marketing Manager. This Keysha's Cookies store provides a variety of flavors as well as cookies biscuits that will be popular, and the like. Keysha's Cookies is located in three different locations as in Pahang is in Kuantan, while in Terengganu we operate in Kuala Terengganu and Melaka we operate in Ayer Keroh. Keysha's Cookies is a store that sells relatively light but delicious food products. This store provides various forms of cookie biscuits that are the choice of customers nowadays and can even be taken everywhere. The difference between our cookies and other companies is that we use a variety of delicious flavors, the design of the design is attractive compared to other companies that look quite familiar for their cookie biscuits. To make it even more interesting, we decided to create some more creativity and innovation by implying creativity and modern elements in each of our products. We have done some research that Malaysia is a developed country made up of people with low income levels and higher income levels. Therefore, we recommend these snacks or biscuit cookies, it is of course Keysha's Cookies to be a shop according to customer tastes, reasonable prices for each customer who comes.